The Effect of Torch Ginger (Etlingera elatior) Flower Extract on Creatinine Levels and Kidney Histophatology in Alloxan-Induced White Rats (Rattus norvegicus) - Nofri Megariang Hura; Erlintan Sinaga (Biology, Medicine, & Natural Product Chemistry, 2025)
Kidney function impairment is a common complication of hyperglycemia, characterized by increased creatinine levels and structural damage to renal tissue. Alloxan is frequently used to induce kidney injury through oxidative stress mechanisms. Torch ginger (Etlingera elatior) flower contains antioxidant compounds with potential nephroprotective effects. This study aims to determine the effect of torch ginger (Etlingera elatior) flower extract on creatinine levels and kidney histopathology in alloxan-induced white rats (Rattus norvegicus). The study used a Completely Randomized Design (CRD) with an experimental approach. The negative control group received destilled water, while the positive control group was induced with alloxan (120 mg/kgBW) intraperitoneally and treated with glibenclamide (0.45 mg/kgBW). The treatments groups (P1, P2, and P3) were given alloxan (120 mg/kgBW) and torch ginger (Etlingera elatior) flower extract orally at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW, respectively. This study showed that torch ginger (Etlingera elatior) flower extract significantly reduced creatinine levels and improved kidney histopathology (renal tubular necrosis). The 400 mg/kgBW dose was the most effective in lowering creatinine levels and repairing kidney tissue damage.